Kamao mga kuwento ng protesta, 1970-1986 - Salanga, Alfrredo Navarro (Center for Literature, Cultural Center of the Philippines, 1987)
An anthology of articles and stories published during the period from just prior to the beginning of Fernand Marcos' presidency through the period immediately after its end.